Pengaruh Insentif terhadap Kinerja Pegawai Negeri Sipil dengan Disiplin sebagai Variabel Moderating: Studi Kasus di Lingkungan Kantor Kementrian Agama Kabupaten Ingragiri Hulu - Nurse Fatimah MZ (STAI Auliaurrasyidin Tembilahan, 2020)
The quality of human resources (HR) of civil servants in government agencies is one of the factors that improve the productivity of an organization or government agencies. One of the factors affecting the performance is incentives and work discipline. Incentives and work discipline are the efforts in improving the quality, quantity, execution of duties and responsibilities of human resources within an organization. This study aims at determining the effect of incentives on the performance of civil servants by work discipline as a moderating variable. This research uses Quantitative Method. Population and sample of this research are Civil Servants at the office of Ministry of Religion of Indragiri Hulu Regency in a total of 34 people. The sampling technique is Census Technique. The Research Method is Explanatory Research, which explains the causal relationship between the independent variable with the dependent variable as the moderating variable. The data collection is performed by the provision of questionnaires and obtains secondary data. Then, data analysis includes descriptive analysis; hypothesis testing that was analyzed by using simple linear regression test and Moderating Regression Analysis (MRA). The results of the study indicated that incentives have a significant effect on performance. Another result that can be concluded is that the work discipline variable as a moderating variable strengthens the influence of the relationship of incentive variable and performance variable of Civil Servant of Indragiri Hulu Ministry of Religious Affairs office. So, the amount of incentive given makes the performance of Civil Servant higher and better when having high work discipline.